The Expression Shifts in the English Translation of Chudori’s Laut Bercerita - Veronika Esther Diah Kurniawati; Harris Hermansyah Setiajid (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
As a means of facilitating access to knowledge and information, translation is critical in providing access to a wide range of subjects, particularly literature. The essence of translation in literature is crucial since, other than making literary work accessible all across the globe; it also enables writers to express themselves across cultures and generations while simultaneously influencing the reader's interpretation of literary works. As an instance of a translation product, the novel, which is a form of literature, can be cited as an example. The process of translating a novel is not just a matter of transferring language but also of disseminating its figurative language as well as determining the appropriate expressions to capture the emotions of the original work. However, translating a novel is more complicated than translating another genre of literature since a writer mainly utilizes a myriad of figurative language in their writing. As a result of this, there is likely an expression shift during the translation of figurative language. Examining expression shifts, which are changes in the way figurative language or expressions are presented when translated from one language to another, in the translation of figurative language within novels is highly relevant, as understanding these shifts can lead to improved translation practices, foster a deeper appreciation of cultural nuances, and better preserve the author's intended meaning across languages. This study strives to discover what types of expression shifts are present in the English translation of the figurative language in Leila S. Chudori's Laut Bercerita. Subsequently, this study is designed to analyze how figurative language is shifting in terms of its values of expression during translation. The data for the analysis are taken from Laut Bercerita (2017) by Leila S. Chudori, along with its English version titled The Sea Speaks His Name (2020), translated by John McGlynn. This novel is selected due to its figurative that is well-written, well-imagined, and easily discernible by readers of all backgrounds. In this study, a contribution will also be made to the field of translation studies, with an emphasis on the shift in expression during the translation of figurative language within a novel.